Analysis of the Impact of the Adiwiyata Program Policy on School Sanitation : A Literature Review - Saputra, Harmedi Yulian; Barlian, Eri; Yuniarti, Elsa; Handayuni, Linda (Jurnal Kesehatan Cendikia Jenius, 2024)
The sanitation conditions in schools across Indonesia vary significantly, with many schools, especially in remote areas, lacking proper sanitation facilities such as clean water, adequate toilets, and hygiene programs. This has a direct impact on students' health, contributing to issues such as diarrhea, dehydration, and malnutrition. Good sanitation is essential as it contributes to students' health and creates a more conducive learning environment. The Adiwiyata School Program, which integrates environmental education and sustainability, plays a crucial role in improving school sanitation by enhancing facilities and changing students' behavior towards cleanliness. This study aims to explore the impact of the Adiwiyata School Program on sanitation in Indonesian schools through a literature review approach. The method used is a literature review to collect data from various sources such as journals, books, and relevant online articles. The findings suggest that the Adiwiyata Program has successfully improved sanitation, particularly in areas like canteen cleanliness, waste management, and the implementation of handwashing practices, although challenges related to budget and awareness still exist. It is recommended that further research be conducted to examine the direct impact of the Adiwiyata Program and the need for increased awareness and budget support to strengthen the program’s effectiveness.